Ecology and Geographical Distribution for Six Species of the Genus Echinops L.(compositae) in Iraq - Al-Musawi , Ali H.; A. Aliwy, Sukeyna (Iraqi Journal of Science, 2023)
This study includes six species related to the genus Echinops L. (composite) grown in Iraq which are listed below: E.armatus Boiss. & Hausskn., E. bicolor Nabelek, E. cephalotes DC., E.haussknechtii Boiss., E. moulensis Rech., E. nitens Bornm., the geographical distribution and ecological preferences' were documented.It has been also observed that this genus was distributed near waterfalls, vallies, road side, dry limestone, clay soil and hard rocky soil in Different heights. The most separated species was E.armatus and the least separated one was E.haussknechtii, the species was listed in diagram and distributed on a map.